Respon Fisiologis dan Metabolit Darah Kambing dan Domba yang Ditransportasi dengan Pick-Up Triple-Deck - Gopar, R. A.; Afnan, R.; Rahayu, S.; Astuti, D. A. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
The overall transportation process is a gripping activity for goats and sheep. Goats and sheep canexperience stress as reflected by indicators of weight loss, physiological responses and blood metabolites.The use of sheep goat and sheep conveyance according to the Regulation of the Minister of Agricultureof the Republic of Indonesia number 114/Permentan/PD.410/9/2014concerning the transportation ofsacrificial animals, vehicles can be designed for a maximum of two decks. Farmers use pick-up vehiclesarranged in three levels to reduce transportation costs. This study uses two triple-deck pick-up vehiclesfor 60 goats and 60 sheep. Each deck is filled with 20 animals and five animals are taken as samples.The design used by using a randomized block design (RBD), the position of the deck (deck 1, deck 2,deck 3) as a factor, and body weight as groups. The evaluation results of goat and sheep transportationwith a distance of ± 674 km (± 16 hours of travel) shows that deck has no significant effect (P>0.05) onthe weight loss of goat and sheep also did not affect (P>0.05) on the physiological response and bloodmetabolites. The stress level of goats and sheep transported is not affected by deck position.